Propuesta de implementación de un sistema de control de inventarios en la industria de aceites y grasas - Zúñiga Molina, Pedro Stéfano (2020)
This project presents an improvement proposal focused on the control and management of inventories for a spare parts warehouse, which is located inside an oil and grease company. This company mainly deals with the extraction and production of palm and palm kernal oils inside Ecuadorian territory. The purpose of this work is to demonstrate the importance of control for the stock rotation inside a warehouse. Due to the fact that the industry does not have the correct inventory control. The company do the ABC classification of each product based on the data collected from 2019. Therefore, it helps to define the important areas in terms of rotation costs of inventories. Once the rotation is determined, a redesign of the layout is carried out. Then, they proceed to the time keeping and to compare the actual distribution to the proposed distribution. In addition, a new inventory system is implemented. It is for the inventory control and management. It allows the warehouse to take constant control of their stock. Ultimately, this work has the comparison between savings and investment costs that would have to be applied in the spare parts warehouse.